The Phytochemical Identification And Antibacterial Activity Test Of Leucas Lavandulifolia Against Escherichia Coli - Nidya Meilani; Dianasari, Dewi; Indah Yulia Ningsih (Journal of Agromedicine and Medical Sciences, 2025)
Diarrhea is defined as a condition where the stool changes or becomes softer or more liquid with a frequency of 3 or 4 times a day. Based on its etiology, diarrhea is caused by several microorganisms, one of which is bacteria. The bacteria that causes diarrhea most often found in Indonesia is Escherichia coli. One type of plant that has the potential as an antibacterial is the Leucas lavandulifolia or Lenglengan plant. Based on ethnopharmaceutical studies, lenglengan leaves are commonly used to treat insomnia, pinworms, coughs with phlegm, epilepsy and digestive disorders. This research was carried out using lenglengan leaf ethanol extract with concentrations of 2.5%, 5%, 10%, 20% and 40%. In this study, phytochemical screening was also carried out using the TLC method. Antibacterial testing was carried out using the well diffusion method. The results obtained were the formation of a clear zone around the well, which indicated activity inhibiting bacterial growth. The results of testing antibacterial activity against E.coli showed that the ethanol extract of langlengan leaves at concentrations of 2.5%, 5%, 10%, 20% and 40% had antibacterial activity with clear zone results of 1.04 ± 0.33 , 12.71 ± 0.34, 13.90 ± 0.60, 15.23 ± 0.36, and 19.32 ± 0.79 mm.  The results of the phytochemical screening showed that ethanol extract of lenglengan leaves contained alkaloids, saponins, flavonoids, terpenoids/steroids and polyphenols. It can be concluded, the ethanol extract of lenglengan leaves has antibacterial activity against E.coli where the greater  sample concentration, the greater  activity.